Weed Management in Sugarcane - Dennis C. Odero; Joan A. Dusky (EDIS, 2021)
This article describes techniques that can be used by growers to make management decisions to help control weeds in sugarcane. Written by D. C. Odero and J. A. Dusky, and published by the UF/IFAS Agronomy Department, revised July 2021.